IMPROVING STUDENTS’ WRITING ON DESCRIPTIVE TEXTS THROUGH MIND MAPPING TECHNIQUE - IDA MAULIDIA (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN, 2018)
The research type was an action research method. This research in subject consisted of 25 students of the eighth grade students of SMP Negeri 3 Kalijati in Subang. The total of this research is 25 students. The problems of this research were student often difficulty in develop their main idea paragraph especially on descriptive texts. The researcher has strategies that find out how to improve writing using mind mapping technique. It is goal of the research not only to know ability student in writing, but also to develop about in improving students’ writing on descriptive texts and also to easier students and teachers of teaching learning process in English lesson through mind mapping technique. Based on the researcher and analysis data collected that differences improved the research data were collected using test (test after first treatment and test after the second treatment), observation for collecting data on the students’ motivation in improving writing texts ability using mind mapping technique. Data on writing on descriptive texts through mind mapping technique were analyzed using the descriptive and statistic analysis, to know the improvement in mean students after the first cycle and the second cycle. Based on the first cycle, the students’ average was 62,2 then, on the second treatment the students’ average was 69,6, the cycle III students’ average increase to be 81,6. Based on the data, that will be concluded that students can improve students’ writing on descriptive texts through mind mapping technique.